2011
DOI: 10.1021/es200587z
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Atmospheric Humic Like Substances by Ozone: A Kinetic and Structural Analysis Approach

Abstract: This work explores the heterogeneous reaction between HUmic-LIke Substances (so-called HULIS) and ozone. Genuine atmospheric HULIS were extracted from aerosol samples collected in Chamonix (France) in winter and used in coated flow tube experiments to evaluate heterogeneous uptake of O₃ on such mixtures. The uptake coefficient (γ) was investigated as a function of pH (from 2.5 to 10), O₃ concentration (from 8 to 33 × 10¹¹ molecules cm⁻³), relative humidity (20 to 65%) and photon flux (from 0 to 1.66 × 10¹⁵ pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 42 publications
5
47
1
Order By: Relevance
“…These are potential ozone sinks and sources of oxygenated VOC in ozone-rich environments, as has been shown previously (see e.g. Wisthaler et al, 2005;Weschler et al, 2007;D'Anna et al, 2009;Wisthaler and Weschler, 2010;Baduel et al, 2011). We speculate that some of the ozonolysis-derived products may play important roles in atmospheric processes, influencing the budgets of OH radicals and ozone.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…These are potential ozone sinks and sources of oxygenated VOC in ozone-rich environments, as has been shown previously (see e.g. Wisthaler et al, 2005;Weschler et al, 2007;D'Anna et al, 2009;Wisthaler and Weschler, 2010;Baduel et al, 2011). We speculate that some of the ozonolysis-derived products may play important roles in atmospheric processes, influencing the budgets of OH radicals and ozone.…”
Section: Discussionsupporting
confidence: 76%
“…Semi-volatile, unsaturated organic species are common on various surfaces including soil with plant litter (Weiss, 2000;Isidorov et al, 2003;Ormeño et al, 2009), aerosols (Rogge et al, 1993;D'Anna et al, 2009;Baduel et al, 2011), man-made structures (Wisthaler et al, 2005;Weschler et al, 2007;Shi and Zhao, 2015), and even human skin (Wisthaler and Weschler, 2010). These are potential ozone sinks and sources of oxygenated VOC in ozone-rich environments, as has been shown previously (see e.g.…”
Section: Discussionsupporting
confidence: 53%
“…The seed particles' composition is assumed to model the main features of (mainly organic) ambient aerosol, containing both complex and simple organics as well as inorganic components, possibly representing aged particles during longrange transport. HAs are considered to be proxy for atmospheric humic-like substances generated from biomass and wood burning because they have similar reactivity under irradiation (21)(22)(23). Dicarboxylic acids represent 4-15% of the total aerosol mass of atmospheric aerosol particles from continental and marine samples (24) and are formed from biomass burning, fossil fuel combustion, cooking, automobile exhaust, and atmospheric reactions of biogenic and anthropogenic VOCs (25).…”
Section: Atmospheric Chemistry | Photoinduced Processesmentioning
confidence: 99%
“…Previous studies have observed that γ can have a linear dependence on VIS and UV photon flux, but some measurements were limited in the VIS photon flux intensity compared to the sun's total VIS irradiance (Stemmler et al, 2006;Jammoul et al, 2008;Brigante et al, 2008;D'Anna et al, 2009;Baduel et al, 2011;Sosedova et al, 2011;Zelenay et al, 2011). Previous studies have also shown that the uptake of gas phase oxidants may follow a Langmuir-Hinshelwood (LH) type reaction mechanism, where the oxidant first adsorbs on the organic substrate and subsequently reacts, yielding γ values that are reduced at high oxidant concentrations (Stemmler et al, 2007;Jammoul et al, 2008;Brigante et al, 2008;D'Anna et al, 2009;Net et al, 2010;Baduel et al, 2011;Sosedova et al, 2011;Zelenay et al, 2011).…”
Section: S M Forrester and D A Knopf: Photosensitised Kinetics Ofmentioning
confidence: 99%
“…Previous studies have also shown that the uptake of gas phase oxidants may follow a Langmuir-Hinshelwood (LH) type reaction mechanism, where the oxidant first adsorbs on the organic substrate and subsequently reacts, yielding γ values that are reduced at high oxidant concentrations (Stemmler et al, 2007;Jammoul et al, 2008;Brigante et al, 2008;D'Anna et al, 2009;Net et al, 2010;Baduel et al, 2011;Sosedova et al, 2011;Zelenay et al, 2011). A recent modelling study by Konovalov et al (2012) indicated that there may be a positive feedback between the O 3 loss rate and O 3 mixing ratio because of this inverse dependence of γ on O 3 concentration (Konovalov et al, 2012).…”
Section: S M Forrester and D A Knopf: Photosensitised Kinetics Ofmentioning
confidence: 99%